Tracheal granulation as a cause of unrecognized airway narrowing - Gaurav Bhatia; Valsamma Abraham; Linjo Louis (Wolters Kluwer Medknow Publications, 2012)
Tracheostomy is one of the most common elective surgical procedures performed in critically ill patients. The most frequent late complication after tracheostomy is the development of granulation tissue, a complication that may cause airway occlusion or result in airway stenosis. We report the successful management of a patient with tracheal granulation presenting as an unrecognised cause of difficulty breathing.